The Choice Between Corporate And Structured Financing: Evidence From New Corporate Borrowings - Pinto, João (2018)
We examine the factors that influence non-financial firms’ choice between corporate financing (CF) and structured finance (SF). Using a sample of 4,970 Western European deals closed between 2000 and 2016, we find that floatation costs, information asymmetry, and renegotiation and liquidation risks affect firms’ financing decisions. Findings also suggest that firms choose SF when they are less creditworthy and seek long-term financing, and that firms resorting to project finance are smaller and less profitable and have lower short-term debt, lower asset tangibility, and less growth opportunities than corporate bond issuers have. Firms that prefer asset securitization to corporate bonds tend to be smaller, more levered, and less profitable and have lower proportions of fixed assets. Finally, findings are consistent with the hypothesis that firms choose asset securitization to reduce funding costs.